1998
DOI: 10.1186/cc129
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of handwritten and computer-assisted prescriptions in an intensive care unit

Abstract: BackgroundWe conducted a prospective comparative study to evaluate the potential benefit of computer-assisted prescribing (CAP). We compared the accuracy, completeness and time use of CAP with that of conventional handwritten prescribing at the intensive care unit (ICU) of the John Radcliffe Hospital, Oxford, UK.ResultsTwenty-five clinicians and 2409 drug entries were evaluated for accuracy, completeness, legibility and time spent prescribing. One hundred and twenty-eight handwritten and 110 CAP charts were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…This was because the electronic prescription could not be completed unless all the required fields were populated. Overall, the findings of this study are in line with the available evidence in that electronic prescription interventions are linked to a notable decline in omission errors [ 13 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 88%
“…This was because the electronic prescription could not be completed unless all the required fields were populated. Overall, the findings of this study are in line with the available evidence in that electronic prescription interventions are linked to a notable decline in omission errors [ 13 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 88%
“…Such errors of duplicated therapy orders were described in other studies on the impact of CPOE. [ 13 , 14 ] In our study, the use of a CPOE system was associated with an increase in duplicated therapy (7/1593 (0.4%) vs 25/1388 (1.8%)). Physicians should however be aware of duplicated therapies as our CPOE system alerts them about these duplicated orders.…”
Section: Discussionmentioning
confidence: 54%
“…[ 32 , 33 ] Similar to our study, Westbrook et al showed that CPOE was efficient in decreasing administration route errors or dosage errors and Evans et al showed elimination of prescriptions in which the route of administration or dosage were missing. [ 13 , 15 ] These types of errors do not seem to be related to substantial negative outcomes for patients, however, they are time-consuming for nurses and their correction by CPOE is therefore relevant. [ 34 ] When a physician prescribes a medication with CPOE, some items must indeed be specified so that the doctor can validate prescription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Duplicate medication orders are one prominent type of medication error that has increased after the implementation of CPOE and other health information technology (health IT) in some contexts. [4][5][6][7][8][9][10][11] For example, a study evaluating medication error and adverse event data found an increase in the frequency of duplicate medication orders after the implementation of CPOE even with duplicate medication alerts, most of which were for identical orders for the same medication. 11 Though there are some nuances, duplicate medication order errors are commonly defined as two or more unintentional active orders for the same medication or medications within the same therapeutic class.…”
mentioning
confidence: 99%